Meningkatkan Manajemen Lifeskill dan Produktivitas pada Siswa SMA Muhammadiyah 8 Ciputat - Ifa Nurmasari; Septi Rostika Anjani; Neneng Tita Amalya; Endah Mawarny; Hamdi Supriadi (Indonesian Journal of Society Engagement, 2022)
A large population is an asset for a nation in improving its quality of life. However, the rate of population growth that is not matched by increases in other fields, such as the economy and other fields, results in the narrowing of employment opportunities which in turn will increase the number of unemployed. In connection with the narrowness of employment opportunities and the large number of unemployed, one of the solutions offered is to provide materials, motivation and skills to high school students. The young generation since school was given lessons, skills about entrepreneurship so that when they graduate from school, they will not only think about applying for jobs or working for other people or companies, but also thinking about how to create jobs. The method used in this Community Service is to provide knowledge, share experiences and provide motivation about entrepreneurship. To increase the life skills of SMA Muhammadiyah 8 Ciputat students, during this PKM activity, the practice of making food that is easy, tastes good and is liked by many people is also carried out. In addition, they are also taught how to properly package food, in order to increase the selling value of the food. This activity is carried out in accordance with health protocols. The results of this Community Service activity showed increased knowledge, insight, motivation experience of SMA Muhammadiyah 8 Ciputat students. In addition, it was seen that was enthusiasm from SMA Muhammadiyah 8 Ciputat students to practice making food that had been taught.